Exploring the landscape of scientific literacy - Linder, Cedric J., 1954- (Teaching and learning in science series., 2011)
Offering new ways to look at the key ideas and practices associated with promoting scientific literacy, this text takes a pragmatic and inclusive perspective on curriculum reform and learning and presents a future vision for science education research and practice.